INVERSE CORRELATION BETWEEN KI67 EXPRESSION AND STEROID RECEPTORS IN PATIENTS WITH BREAST CARCINOMA - Zivkovic, Ognjen; Milicevic, Andjela; Petrovic, Ivana; Rakocevic, Jelena; Inic, Zorka; Dundjerovic, Dusko; Opric, Dejan; Tatic, Svetislav; Labudovic Borovic, Milica; Ristic, Svetlana; Buta, Marko (Medicinski časopis, 2024)
Aim. The aim of this study is to evaluate the relationship between the immunohistochemical score of cell proliferation index Ki-67 and steroid receptor in patients with a pathohistological diagnosis of breast cancer. The impact of neoadjuvant therapy on biological markers in breast cancer remains controversial.Methods. All patients with invasive breast cancer, as the primary and only malignancy, who underwent surgical and neoadjuvant therapy at the Institute of Oncology and Radiology of the Republic of Serbia (IORS) between 2017 and 2019 were included in the retrospective study. The expression level of Ki-67 and steroid receptors was detected by immunohistochemical analysis. Data were collected in an Excel database and analysed in the statistical softwer SPSS program version 25. For statistical data processing Chi-squared test, Kruskal-Wallis test and Mann-Whitney U test were used. For all statistical analysis, a p
Keywords: breast cancer, neoadjuvant therapy, ER, PR, Ki-67